Pengaruh Antioksidan dan Kombinasi Pengawet terhadap Stabilitas Ekstrak Cair NADES Biji Kopi Hijau - Ramadon, Delly; Septiani, Rosalina Mesusi; Putri, Salsabila Nursyifa; Mun'im, Abdul (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2021)
Green coffee beans (Coffea canephora Pierre ex A. Froehner) contain caffeine and chlorogenic acid which are beneficial for health. These two main ingredients can be extracted using Natural Deep Eutectic Solvents (NADES) in combination with the Ultrasound-Assisted Extraction (UAE) method which is environmentally friendly. NADES can be used for extracting green coffee beans, but the solvent cannot be evaporated, thus the result is a liquid extract. During storage, liquid extracts are susceptible to oxidation and bacterial growth so that they can disrupt physical, chemical, and microbiological stabilities. In this study, butylated hydroxytoluene (BHT) was added as a synthetic antioxidant and a combination of methylparaben-propylparaben as preservative to determine its effect on the physical, chemical, and microbiological stability of the NADES liquid extract of green coffee beans, as well as to determine the best storage temperature. The concentrations of BHT added in this study were 10, 20, and 30 ppm. The concentration of the methyl paraben:propyl paraben combination added was 110:55 ppm, 100:50 ppm, and 90:45 ppm. Each extract was stored at storage temperatures of -20°C ± 5°C, 5°C ± 3°C, and 30°C ± 2°C for 54 days. The results showed that the liquid extract added with 30 ppm BHT concentration and a combination of preservatives with a concentration of 110:55 ppm and stored at a storage with the temperature of -20°C ± 5°C which had the best physical, chemical, and microbiological stability. This shows that the addition of BHT and a combination of preservatives can increase the stability of the green coffee bean NADES extract.